Towards Next Generation Adenosine A2A Receptor Antagonists - Yuan, G.; Jones, G.B. (Current Medicinal Chemistry, 2014)
The Adenosine A2A receptor is a member of the G-protein coupled receptor superfamily. It plays a key role in numerous physiological processes through the central nervous system and in peripheral tissues. Functional interactions between the A2A and dopamine D2 receptor has spurred interest in the use of antagonists as anti-Parkinson drugs. Additionally, oncology drugs are now being designed based on the potential for A2A antagonists to function as immunotherapeutics. From early studies based on classical xanthine type A2A antagonists through second generation agents, this mini review will cover aspects of the discovery, development, chemical synthesis and medicinal evaluation of this important class of drugs.
Keywords: aqueous solubility